Sufism as a Therapy in the Modern Life - Hoerul Umam; Iyad Suryadi (International Journal of Nusantara Islam, 2019)
Sufism or Taṣawwuf is an ancient fruit of Islamic civilization, but experienced revitalization in this modern era. His presence was increasingly meaningful when he was able to become an "oasis in the desert" for modern people who are experiencing a spiritual crisis. In the form of a particular tarekat (ṭarīqah) or a modified form, Sufism has become a medicine for modernization with all its adverse effects. Sufism with spiritual teachings and noble character increasingly plays an important role. He who was once accused of the cause of Islamic decline, and negatively addressed by some Islamic experts, is now increasingly gaining a place in modern society. It is a solution that is anticipated for the problems of contemporary society. By using a literature study, this article was written to contribute to the phenomenon. Its findings, in addition to using scientific and technological instruments, modern life should also be accompanied by mental, spiritual instruments and morality, which are explained in Sufism.